MANAJEMEN KOMPLAIN DAN PENANGANAN KELUHAN DALAM PELAYANAN PUBLIK - Muhammad Taufiq Razali (PROGRAM STUDI ILMU ADMINISTRASI NEGARA. UNIVERSITAS KARIMUN, 2024)
The handling and the management of complaint in public service is an effort made to create a clean and efficient government. This is intended to increase the welfare and create the justice and certainty to fulfill the needs of public as citizens. For the reasons of the sustainability of giving public service and protecting the citizens’ rights from the possibility of doing disabuse in the practice of public service, it is necessary to have the management of complaint, and the management the conflicts which may arise among the public and bureaucracy.